Incidence of Gunshot Wounds: Before and After Implementation of a Shall Issue Conceal Carry Law - Nicholas, Christina M. (Kans J Med, 2020)
INTRODUCTION: This study examined the incidence of gunshot wounds before and after enacting a conceal carry (CC) law in a predominately rural state. METHODS: A retrospective review was conducted of all patients who were admitted with a gunshot injury to a Level I trauma center. Patient data collected included demographics, injury details, hospital course, and discharge destination. RESULTS: Among the 238 patients included, 44.6% (n = 107) were admitted during the pre-CC period and 55.4% (n = 131) in the post-CC period. No demographic differences were noted between the two periods except for an increase in uninsured patients from 43.0% vs 61.1% (p = 0.020). Compared to pre-CC patients, post-CC patients experienced a trend toward increased abdominal injury (11.2% vs 20.6%, p = 0.051) and increased vascular injuries (11.2% vs 22.1%, p = 0.026) while lower extremity injuries decreased significantly (38.3% vs 26.0%, p = 0.041). Positive focused assessment with sonography in trauma (FAST) exams (2.2% vs 16.8, p < 0.001), intensive care unit admission (26.2% vs 42.0%, p = 0.011) and need for ventilator support (11.2% vs 22.1%, p = 0.026) all increased during the post-CC period. In-hospital mortality more than doubled (8.4% vs 18.3%, p = 0.028) across the pre- and post-CC time periods. CONCLUSION: Implementation of a CC law was not associated with a decrease in the overall number of penetrating injuries or a decrease in mortality.